Assessment of high-sensitive methods for the detection of EGFR mutations in circulating free tumor DNA from NSCLC patients. (July 2015) - Pasquale, Raffaella; Fenizia, Francesca; Esposito Abate, Riziero; Sacco, Alessandra; Esposito, Claudia; Forgione, Laura; Rachiglio, Anna Maria; Bevilacqua, Simona; Montanino, Agnese; Franco, Renato; Rocco, Gaetano; Botti, Gerardo; et al.
Aim: We assessed the ability of the Therascreen ® kit (plasma-Therascreen) and of a peptide nucleic acids (PNA)-clamp approach to detect EGFR mutations in plasma-derived circulating-free tumor DNA (cftDNA) from non-small-cell lung cancer patients.Materials & methods: cftDNA from 96 patients was analyzed for exon 19 deletions and the p.L858R mutation, using both plasma-Therascreen and PNA-clamp-based assays.Results: None of the 70 EGFR wild-type patients showed EGFR mutations in cftDNA with both techniques (specificity: 100%). In 17/26 EGFR -mutant patients, plasma-Therascreen analysis confirmed the mutation identified in the primary tumor (analytical sensitivity: 65.4%). Similar results were obtained with the PNA-clamp method.Conclusion: Both approaches were specific and sensitive for EGFR mutational analysis of cftDNA in non-small-cell lung cancer patients.